2007
DOI: 10.1111/j.1472-765x.2007.02235.x
|View full text |Cite
|
Sign up to set email alerts
|

Variants of eae and stx genes of atypical enteropathogenic Escherichia coli and non-O157 Shiga toxin-producing Escherichia coli from calves

Abstract: Aims:  To determine the subtypes of stx and eae genes of Shiga toxin‐producing Escherichia coli (STEC) and enteropathogenic Escherichia coli (EPEC) from calves and to ascertain the typical and atypical nature of EPEC. Methods and Results:  One hundred and eighty‐seven faecal samples from 134 diarrhoeic and 53 healthy calves were investigated for the presence of stx, eae and ehxA virulence genes by polymerase chain reaction and enzyme‐linked immunosorbent assay. Subtype analysis of stx1 exhibited stx1c in 13 (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Several studies reported identifi cation of EHEC O157:H7 through various approaches to detect the toxin genes like, stx1, stx2, eaeA, rfbE, Z3276, hlyA and serogroupspecifi c genes wzx and wzy [Sharma & Dean-Nystrom, 2003;Wani et al, 2007]. Most of these genes are not very unique for the pathogenic serotypes like EHEC O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported identifi cation of EHEC O157:H7 through various approaches to detect the toxin genes like, stx1, stx2, eaeA, rfbE, Z3276, hlyA and serogroupspecifi c genes wzx and wzy [Sharma & Dean-Nystrom, 2003;Wani et al, 2007]. Most of these genes are not very unique for the pathogenic serotypes like EHEC O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of reports on the isolation of aEPEC from a wide range of diarrheic and healthy animal species have been published. In most of the cases, these aEPEC strains have been identified in the course of characterization of A/E E. coli isolates among animals used for food production, such as cattle, sheep, goat, pig and poultry (Aidar et al, 2000;Aktan et al, 2004;Stephan et al, 2004;Blanco et al, 2005;Krause et al, 2005;Leomil et al, 2005;Yuste et al, 2006;Ishii et al, 2007;Wani et al, 2007). Moreover, the detection of aEPEC in domestic animals (dog and cat), horse, deer and marmoset has also been described (Beaudry et al, 1996;Goffaux et al, 2000;Carvalho et al, 2003;Nakazato et al, 2004;Krause et al, 2005;Ishii et al, 2007;A.…”
Section: Transmission and Reservoirmentioning
confidence: 99%
“…As such, it is important to know, which virulence genes, phylogroups, serogroups, and antibiotic resistance patterns are present in commensal E. coli strains in yaks with diarrheic infections. Ruminants act as one of the most important reservoirs for pathogenic E. coli and lead to asymptomatic infections that can cause life-threatening complications in humans [5, 6]. Therefore, this bacterium in yaks with diarrhea may be a potential health risk if it is transmitted to humans via cross-contamination of water, food, carcasses, or feces [7].…”
Section: Introductionmentioning
confidence: 99%